PROMOTING DEVELOPMENT PROGRAM EFFECTIVENESS: THE EXPECTED ROLE OF PUBLIC SECTOR AUDIT IN STATE FINANCE MANAGEMENT - Wibowo, Andi (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2019)
Public sector audit has an important role in development by improving transparency and accountability of state finance management. It is observed, however, that many development programs do not meet their objectives. It indicates that the current public sector audit has not been adequate to promote development program effectiveness. The objective of this research is to confirm whether the current public sector audit approach is not adequate to promote development program effectiveness and what additional roles are expected to be fulfilled by public sector audit. This study is based on the Indonesian context and uses a qualitative methodology where 27 semi-structured interviews were conducted to Member of Parliament and officials of the Supreme Audit Institution (SAI) and government entities in Indonesia. The study shows that the existing public sector audit has not been adequate to promote development program effectiveness because it pays more attention to financial and compliance aspects of the development program. Moreover, it also focuses on a completed development program. Stakeholders expect that public sector audit also needs to provide the solution, provide preventive measures, create a good environment and produce useful information for decision making.